Nature-based Learning Management in Improving Children's Natural Intelligence - Tobroni, Tobroni; Munaji, Munaji; Rozi, Fathor; Rofi'ah, Alifatur; Fadilah, Nurul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to analyze children's natural intelligence improvement through nature-based learning management at RA Al Khodijah Probolinggo. The research method used is a qualitative case study type. Researchers conducted observations, interviews with principals and teachers, and documentation. Data analysis in this study begins with data collection and reduction and continues with concluding. The results show that nature-based learning effectively increases the natural intelligence of early childhood through nature-based learning, which is an introduction to forms of love for nature or the surrounding environment, such as visiting the zoo, planting trees, and others. Nature-based learning uses nature as teaching material, a place to learn and learn objects, with the concept of a natural school. Students are expected to be able to learn with nature and be able to connect and apply the knowledge gained in real, everyday life.